Roberta Rambelli: una presencia invisible (Altre Modernità, 2018)
Roberta Rambelli was one of the first Italian science fiction writers, editor of the «Galassia» pulp book series, creator of the first collection of “serious” science fiction books and one of the most acclaimed translator of American best-seller novels. Nevertheless, her work and figure has been largely overlooked by academics in both literature and science fiction studies. The objective of this article is to analyze Rambelli’s professional career as writer, editor and translator while aiming to reconstruct the possible causes of this neglect. In order to do this, we have linked a descriptive term to each of her activities: as writer, disguise; as editor, exclusion; as translator, invisibility. This labelling device will serve the purpose of organizing, connecting and elucidate the elements and causes of what we have defined as a Rambelli tendency to shroud and be shrouded.
Keywords: Roberta Rambelli; Italian science fiction; women writers; translation studies; polysystem theory